Pengaruh Penyetelan Squeezing Roll Pada Mesin Sizing Terhadap Kekuatan Benang - Filly Pravitasari; Afriani Kusumadewi (Universitas Insan Cendekia Mandiri, 2021)
The process of applying starch to the warp yarn in order to increase the weaving power of the warp yarn in the presence of a starch layer, is expected to increase the strength of the yarn and reduce the yarn hairs. One of the factors that influence the sizing process is the amount of pressure in the squeezing roll. In this process, the sizing machine uses a double size box and each size box has 2 (two) squeezing rolls. The material used is Combed Ne 40 yarn with construction ,which is the amount of tetal or the density of the yarn with the construction included in the tetal of the dense warp yarn. The method used by comparing the pressure of squeezing roll process 1 and process 2. In the first process, the squeezing roll 1 is set at 3 kN and squeezing roll 2 is 3.5 kN, while in the second sizing process, the squeezing roll 1 is set at 4 kN and squeezing roll 2 for 5kN. After the experimental process was carried out, the starch warp yarn strength was obtained which was higher, namely 351.93gr and compared to process 2 which was 345.84 gr. The higher from the strength of the starchy yarn, can make it better for weaving process.